Influence of TiO2 and Si on the exciton–phonon interaction in PbI2 and CdS semiconductors evidenced by Raman spectroscopy. (7th August 2017) - Nila, A; Baltog, I; Dragoman, D; Baibarac, M; Mercioniu, I
Abstract: The exciton–phonon interaction, considered as a stimulated Raman scattering process, is studied in different semiconductor mixtures: PbI2 /TiO2, PbI2 /Si and CdS/Si. Raman spectra recorded at excitation wavelengths of 514.5 and 488 nm for PbI2 and CdS, respectively, reveal a strong enhancement of the Raman lines peaked at 97 and 305 cm −1, evaluated by the ratio I TK / I 300 K between the relative intensities of the spectra recorded in the temperature range of 88–300 K. It is found that PbI2 and CdS exhibit a decrease in the Raman intensity modes with decreasing temperature, while in TiO2 and Si an increase in the Raman lines intensities peaked at 138 and 520 cm −1 is observed. This behavior can be explained by an energy transfer process from PbI2 or CdS towards TiO2 and Si. This explanation is supported by the schematic potential energy levels diagram obtained from the density of states, which is calculated using the density functional theory. According to this energy levels diagram, the electrons are expected to migrate directly from the conduction band (CB) energetic levels of the PbI2 and CdS towards the CB levels of TiO2 and Si.